2019
DOI: 10.1111/jcpe.13085
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of the effect of periodontal treatment on cardiovascular risk biomarkers in patients with stable coronary artery disease: Preliminary findings of 3 months

Abstract: Aim: To assess the effect of periodontal therapy (PT) on cardiovascular blood biomarkers. Materials and Methods: This single-blind, parallel-design, randomized controlled trial included patients with stable coronary artery disease and periodontitis. The test group (TG) received non-surgical PT, whereas the control group (CG) received one session of plaque removal. Plasma levels of C-reactive protein (CRP), glycated haemoglobin, lipids and cytokines (IL-1β, IL-6, IL-8, IL-10, IFNγ and TNFα) were measured at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
1
34
2
Order By: Relevance
“…A small RCT on the effects of the treatment of periodontitis on CVD biomarkers in patients with established CVD (Montenegro et al, ) showed no cardiovascular adverse events within 3 months of completion of scaling and root planing (periodontal therapy).…”
Section: Cardiovascular Risks and Complications Of Periodontal Therapmentioning
confidence: 99%
“…A small RCT on the effects of the treatment of periodontitis on CVD biomarkers in patients with established CVD (Montenegro et al, ) showed no cardiovascular adverse events within 3 months of completion of scaling and root planing (periodontal therapy).…”
Section: Cardiovascular Risks and Complications Of Periodontal Therapmentioning
confidence: 99%
“…A small RCT on the effects of the treatment of periodontitis on CVD biomarkers in patients with established CVD [80] showed no cardiovascular adverse events within three months of completion of scaling and root planing (periodontal therapy).…”
Section: In Patients With Established Cvdmentioning
confidence: 99%
“…14,15 As a result of the host-mediated immune response against the microbial challenge, serum concentrations of inflammatory mediators, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and prostaglandin E2 (PGE2), elevate in periodontal disease. 16 These mediators trigger atherosclerosis by recruiting inflammatory cells to blood vessels, proliferating vascular smooth muscle cells, and inducing vascular fat degeneration and intravascular coagulation (indirect mechanism). 17 Loss of tooth is one different substantial condition which has an impact on systemic health.…”
Section: Introductionmentioning
confidence: 99%